Food system activism and the housing crisis - Pine, Adam (Journal of Agriculture, Food Systems, and Community Development, 2022)
The affordable housing crisis in the United States is leaving millions of Americans homeless or spending over one-third of their income on rent, a condition housing scholars refer to as ‘shelter poverty.’ This problem has clear linkages to the food system in terms of the cost and condition of food workers’ housing, the availability of food in low-income neighborhoods, the relationship between food and housing policy, and how much money households have available to provision themselves after paying rent. This commentary explores four aspects of the relationship between the U.S. food and housing systems: the contradiction between abundance and scarcity; the role of racism and coloniality in creating these systems; the role of the government and public policy in maintaining and supporting these systems; and how stigma affixes itself to both the hungry and the shelter-poor. Incorporating housing as part of food system work can strengthen both ongoing movements and unite scholars and activists in exploring the on-the-ground living experiences of people across the country.